2023
DOI: 10.3233/adr-230038
|View full text |Cite
|
Sign up to set email alerts
|

TgF344-AD Rat Model of Alzheimer’s Disease: Spatial Disorientation and Asymmetry in Hemispheric Neurodegeneration

Boriss Sagalajev,
Lina Lennartz,
Lukas Vieth
et al.

Abstract: Background: The TgF344-AD ratline represents a transgenic animal model of Alzheimer’s disease. We previously reported spatial memory impairment in TgF344-AD rats, yet the underlying mechanism remained unknown. We, therefore, set out to determine if spatial memory impairment in TgF344-AD rats is attributed to spatial disorientation. Also, we aimed to investigate whether TgF344-AD rats exhibit signs of asymmetry in hemispheric neurodegeneration, similar to what is reported in spatially disoriented AD patients. F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…Another study found that TgF344-AD rats develop strong preference for one of the two levers, that prevented memory assessment with DMTP in 50% of rats (Sagalajev et al, 2023). In AD-rats that did not develop lever-preferences, and no spatial short-term memory impairments were observed on either DMTP (Sagalajev et al, 2023) or DNMTP (Muñoz-Moreno et al, 2018). Those studies did not include sex as a factor, which we show can influence this behavioral assay.…”
Section: Sex Influences the Behavioral Consequences Of Developmental ...mentioning
confidence: 75%
See 1 more Smart Citation
“…Another study found that TgF344-AD rats develop strong preference for one of the two levers, that prevented memory assessment with DMTP in 50% of rats (Sagalajev et al, 2023). In AD-rats that did not develop lever-preferences, and no spatial short-term memory impairments were observed on either DMTP (Sagalajev et al, 2023) or DNMTP (Muñoz-Moreno et al, 2018). Those studies did not include sex as a factor, which we show can influence this behavioral assay.…”
Section: Sex Influences the Behavioral Consequences Of Developmental ...mentioning
confidence: 75%
“…In contrast, the opposite effect was found in male rats: AIE and AD transgenes improved short-term memory performance. Another study found that TgF344-AD rats develop strong preference for one of the two levers, that prevented memory assessment with DMTP in 50% of rats (Sagalajev et al, 2023). In AD-rats that did not develop lever-preferences, and no spatial short-term memory impairments were observed on either DMTP (Sagalajev et al, 2023) or DNMTP (Muñoz-Moreno et al, 2018).…”
Section: Sex Influences the Behavioral Consequences Of Developmental ...mentioning
confidence: 99%